Harmonizing Humanity: The Enduring Legacy of Performing Arts in Character Education Through Literary Anthropology - J. Polii, Intama; Al-Katuuk, Kamajaya; Waridin, Aulia Anggriani (Center of Language Development, Institut Agama Islam Negeri Madura, 2024)
Indonesia has a rich cultural diversity, but some traditions, such as the Dames performing arts of the Javanese Tondano community in Minahasa, are fading due to external cultural influences; therefore, preservation efforts are crucial to maintain this valuable cultural heritage and its role in fostering social harmony and character values. This research aims to determine the local wisdom values of the Dames performing arts in the Javanese Tondano community in Minahasa. The mixed marriage between the Tondano Javanese people and the native Minahasa people combines two different cultural tribes so that through performing arts, Dames can unite these two cultural tribes. Preservation in this research means creating and maintaining intangible cultural heritage from ancestors so that the community members can remember their cultural identity. We determine the artistic elements in academic studies through literary anthropology as a distinguishing tool in this research. The research methodology used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results obtained in this research are regional wisdom values in four performing arts song lyrics Dames, namely: 1) values related to God, humility, and unity in the lyrics of the song Now It's Even, 2) values related to courtesy, honesty, and cooperation in the lyrics of the song Salam We Are Together, 3) values regional wisdom related to tolerance, harmony and love of peace in the lyrics of the song Thank You, and 3) regional wisdom values related to caring and strengthening in the lyrics of the song Asaranu My goal. Through these local wisdom values, the implications of the value of character education for students at school are also obtained.